Nasal microbiome research in ANCA-associated vasculitis: Strengths, limitations, and future directions - Andreas Kronbichler; Ewan M. Harrison; Josef Wagner (Computational and Structural Biotechnology Journal, 2021)
The human nasal microbiome is characterized by biodiversity and undergoes changes during the span of life. In granulomatosis with polyangiitis (GPA), the persistent nasal colonization by Staphylococcus aureus (S. aureus) assessed by culture-based detection methods has been associated with increased relapse frequency. Different research groups have characterized the nasal microbiome in patients with GPA and found that patients have a distinct nasal microbiome compared to controls, but the reported results between studies differed. In order to increase comparability, there is a need to standardize patient selection, sample preparation, and analytical methodology; particularly as low biomass samples like those obtained by nasal swabbing are impacted by reagent contamination. Optimization in obtaining a sample and processing with the inclusion of critical controls is needed for consistent comparative studies. Ongoing studies will analyze the nasal microbiome in GPA in a longitudinal way and the results will inform whether or not targeted antimicrobial management in a clinical trial should be pursued or not. This review focuses on the proposed role of S. aureus in GPA, the (healthy) nasal microbiome, findings in the first pilot studies in GPA, and will discuss future strategies.